Sistem Monitoring Peninjauan Kapasitas Sampah Via Telegram Berbasis Internet Of Things Dengan Application Development - Okta Rina, Tiara; Fauzan, M Nur; Ocsirendi, Ocsirendi; Yudhi, Yudhi (Jurnal Inovasi Teknologi Terapan, 2025)
Internet of things (IoT) is a concept where various physical devices are interconnected and communicate through the internet. These devices can also be managed through applications on smartphones, not only that IoT can also collect data from the surrounding environment through sensors from this data can be analyzed to provide insight or automate actions. The sensors in this final project include loadcell sensors, MQ-135 sensors, and ultrasonic sensors. The method used is the application development method which refers to a systematic approach used in designing, developing, testing, and implementing application software. The results show that using the application development method can be easily understood by users, one of the application software that can be applied is the telegram application. The system must be designed to collect, process, and send data efficiently, including proper sensor calibration and system tests to ensure accuracy. In addition, it is necessary to implement a reliable communication system to report information in real-time and provide a monitoring system that can provide appropriate notifications and analysis.